"All is well": professionals' documentation of social determinants of health in Swedish Child Health Services health records concerning maltreated children - a mixed method approach. Issue 1 (December 2016) - Köhler, Marie; Rosvall, Maria; Emmelin, Maria
Abstract Background Knowledge about social determinants of health has influenced global health strategies, including early childhood interventions. Some psychosocial circumstances – such as poverty, parental mental health problems, abuse and partner violence – increase the risk of child maltreatment and neglect. Healthcare professionals' awareness of psychosocial issues is of special interest, since they both have the possibility and the obligation to identify vulnerable children. Methods Child Health Services health records of 100 children in Malmö, Sweden, who had been placed in, or were to be placed in family foster care, were compared with health records of a matched comparison group of 100 children who were not placed in care. A mixed-method approach integrating quantitative and qualitative analysis was applied. Results The documentation about the foster care group was more voluminous than for the comparison group. The content was problem-oriented and dominated by severe parental health and social problems, while the child's own experiences were neglected. The professionals documented interaction with healthcare and social functions, but very few reports to the Social Services were noted. For both groups, notes about social structures were almost absent. Conclusions Child Health Service professionals facing vulnerable children document parental health issues and interaction with healthcare, but they fail to document living conditions thereby making social structures invisible in the health records. The child perspective is insufficiently integrated in the documentation and serious child protection needs remain unmet, if professionals avoid reporting to Social Services.